FINANCIAL LITERACY IN THE ERA OF DIGITAL RISKS: A STRATEGY FOR PROTECTING THE POPULATION OF UZBEKISTAN FROM DIGITAL FRAUD - Nurullina Kamila Rustamovna (Modern American Journals, 2025)
In the context of accelerated digitalization of the financial sector, the issue of improving financial literacy among the population becomes critically important. The article examines the main manifestations of digital fraud relevant to the Republic of Uzbekistan and proposes comprehensive approaches to counteracting cyber threats. Specifically, the study analyzes legislative initiatives, financial education programs, and technological solutions aimed at enhancing the protection of financial service consumers. Special attention is given to the need for coordinated actions between government structures, financial institutions, and society as a whole.
Keywords: Financial literacy, digital fraud, cyber threats, consumer protection, digital transformation